A thousand on-line strategies and tools in academic addiction specialty education in post-COVID time: from necessity to quality - Henriques, Susana (2022)
The COVID pandemic has accelerated digitalization of education. Regarding academic addictions speciality programmes we first responded out of necessity. In a second moment, more recent, there are innovation and quality concern. This structured session focus on online training programmes of addictions and has the following aims: - Sharing good practices in moving from necessity to quality; - Discussing where on-line strategies can be helpful, appropriate and supportive towards trend of exponential growing academic degree addiction specialty programmes - Discussing further developments regarding innovation, quality...